2005
DOI: 10.1111/j.1745-4603.2005.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

RHEOLOGICAL BEHAVIOR OF POMEGRANATE (PUNICA GRANATUM L.) JUICE AND CONCENTRATE

Abstract: The rheological behavior of pomegranate juice (Punica granatum L.), prepared from fresh pomegranates, was studied as a function of solids concentration in the range 17.5–75°Brix at 10–55C, using a controlled stress rheometer. Concentration methods did not influence flow behavior. There were no significant differences (P > 0.05) between viscosity and activation energy values for the pomegranate juices concentrated by different methods. The juices exhibited Newtonian behavior regardless of the concentration meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 13 publications
9
60
0
1
Order By: Relevance
“…Similar type of exponential relation was reported relating to flow activation energy to total soluble solid content. The magnitude of the coefficient concentration was found to be 0.049 and it was within the range as reported for different fruit juices such as pomegranate, pineapple, cherry, peach, chokeberry, lime, gooseberry and tender coconut water (Altan and Maskan 2005;Kaya and Sozer 2005;Shamsudin et al 2007;Giner et al 1996;Ibarz et al 1992a;Juszczak et al 2009: Manjunatha et al 2012a2012b;Manjunatha and Raju 2013). It was reported that flow activation energy increased significantly with square of total soluble solid content for blue berry and raspberry juices, where as it increased quadratically with soluble solid content in case of liquorice (Glycyrrhiza glabra ) extract (Nindo et al 2005;Maskan 1999).…”
Section: Effect Of Temperaturementioning
confidence: 68%
See 2 more Smart Citations
“…Similar type of exponential relation was reported relating to flow activation energy to total soluble solid content. The magnitude of the coefficient concentration was found to be 0.049 and it was within the range as reported for different fruit juices such as pomegranate, pineapple, cherry, peach, chokeberry, lime, gooseberry and tender coconut water (Altan and Maskan 2005;Kaya and Sozer 2005;Shamsudin et al 2007;Giner et al 1996;Ibarz et al 1992a;Juszczak et al 2009: Manjunatha et al 2012a2012b;Manjunatha and Raju 2013). It was reported that flow activation energy increased significantly with square of total soluble solid content for blue berry and raspberry juices, where as it increased quadratically with soluble solid content in case of liquorice (Glycyrrhiza glabra ) extract (Nindo et al 2005;Maskan 1999).…”
Section: Effect Of Temperaturementioning
confidence: 68%
“…The consistency coefficient k is increased with total soluble solid content as well as particle size and is decreased with increase temperature of watermelon juice (Sogi et al 2010). The viscosity of pomegranate juice is significantly affected by total soluble content and temperature while it was not affected by concentration method (Altan and Maskan 2005). The viscosity of goldenberry juice was markedly affected by enzyme treatment and as well as temperature (Sharoba and Ramadan 2011).…”
Section: Physicochemical Characteristicsmentioning
confidence: 84%
See 1 more Smart Citation
“…Several investigators reported that clarified and depectinated juices and their concentrates exhibit Newtonian flow behaviour (Ibarz et al 1987(Ibarz et al , 1992aCepeda & Villaran 1999;Juszczak & Fortuna 2004). Several authors used Newtonian equation for describing rheological behaviour of food products such as Pomegranate juice (Altan & Maskan 2005), Pekmez (Kaya & Balibagli 2002), Liquorice extract (Maskan 1999), however, certain juices with a low pulp content and soluble solid content less than 30 o Brix also behave like a Newtonian liquid (Krokida et al 2001) described as:…”
mentioning
confidence: 99%
“…Em geral, o efeito da temperatura na viscosidade aparente (η a ), a uma taxa de deformação específica, tem sido expresso por uma equação do tipo Arrhenius (Altan & Maskan, 2005;Grigelmo-Miguel et al, 1999;Magerramov et al, 2007;Togrul & Arslan, 2004), como mostrada na Equação 3.…”
Section: Effect Of Temperature and Shear Rate In The Properties Of Whunclassified